Morphometrics of Adult Chinese Citrus Fly Bactrocera minax (Enderlein) (Diptera: Tephritidae) in Nepal - Adhikari, D; Thapa, R B; Joshi, S L; Du, J J (Journal of the Plant Protection Society, 2022)
Morphometric study of adult Chinese citrus fly, Bactrocera minax (Enderlein) was carried out on May, 2020 at Sindhuli, Nepal. The mean body length of female recorded significantly higher, 14.29 ± 0.20 mm, than male, 12.52 ± 0.26 mm, with the mean difference of 1.77 mm (p = ≤ 0.001). Females had a wider body (3.90 ± 0.06 mm) compared to males (3.39 ± 0.05 mm) (p = ≤ 0.001) which differed significantly by 0.51 mm. Adult female possessed a wider wingspan, i.e. 23.51 ± 0.23 mm significantly different than adult male, i.e. 22.80 ± 0.19 mm with the mean difference of 0.71 mm (p = ≤ 0.05). Similarly, the average wing length measured 8.82 ± 0.13mm in male and 9.05 ± 0.11 mm in female with the mean difference of 0.23 mm. The ovipositor length recorded 4.52 ± 0.12 mm. This information is useful to distinguish between Chinese citrus fly and other fruit fly species of citrus orchards and useful in planning of the suitable management options.